Supplementation of lactic acid bacteria has positive effects on the mucosal health of Atlantic salmon (Salmo salar) fed soybean meal - Nimalan, Nadanasabesan; Sørensen, Solveig Lysfjord; Fečkaninová, Adriána; Koščová, Jana; Mudroňová, Dagmar; Gancarčíková, Soňa; Vatsos, Ioannis; Saraswathy, Bisa; Kiron, Viswanath; Sørensen, Mette (Aquaculture Reports, 2023)
publishedVersion